2016
DOI: 10.1111/1755-0998.12518
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Atlantic mackerel inferred from RAD‐seq‐derived SNP markers: effects of sequence clustering parameters and hierarchical SNP selection

Abstract: Restriction‐site‐associated DNA sequencing (RAD‐seq) and related methods are revolutionizing the field of population genomics in nonmodel organisms as they allow generating an unprecedented number of single nucleotide polymorphisms (SNPs) even when no genomic information is available. Yet, RAD‐seq data analyses rely on assumptions on nature and number of nucleotide variants present in a single locus, the choice of which may lead to an under‐ or overestimated number of SNPs and/or to incorrectly called genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 50 publications
7
69
1
Order By: Relevance
“…Additionally, we found that the presence of large numbers of singleton SNPs drowned out the signal of genetic differentiation, as observed previously by Rodríguez‐Ezpeleta et al. (2016). This resulted in STRUCTURE plots with no differentiation between populations (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that the presence of large numbers of singleton SNPs drowned out the signal of genetic differentiation, as observed previously by Rodríguez‐Ezpeleta et al. (2016). This resulted in STRUCTURE plots with no differentiation between populations (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The robustness of relative F ST values that reflect relationships or clustering patterns have also been shown despite changes in absolute values with different mismatch parameter settings during SNP loci clustering [83]. Nevertheless, the absolute F ST values obtained in this study should be cautiously interpreted because the inclusion of only a subset of 10–12 samples per population in SNP analyses may have resulted in an over-estimation of pairwise F ST values (sample sizes smaller than 4–6; [84]).…”
Section: Discussionmentioning
confidence: 99%
“…Although the marine environment is relatively homogeneous compared with freshwater, numerous studies have revealed that differential thermal tolerance may result in ecological adaptation in marine species 5, 20 . Moreover, with the development of sequencing techniques, a growing number of studies using a high number of genome-wide polymorphic makers suggest that marine populations are not as connected as might be presumed 21, 22 . Hence, these techniques allow for inference of neutral population structure and also provide information on local adaptation or speciation events 19, 22, 23 .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the GBS technique and related approaches have been used to investigate the genetic structure and local adaptation in marine fish species, such as sailfin molly Poecilia latipinna 25 , ide Leuciscus idus 26 , threespine stickleback Gasterosteus aculeatus 27, 28 , small yellow croaker Larimichthys polyactis 22 , and Atlantic mackerel Scomber scombrus L 21 . Using such methods to investigate populations undergoing ecological divergence is particularly useful because these techniques provide good opportunities to detect genomic loci under divergence selection 5 , and such loci are expected to stand out with high F st estimates against a background of low genetic divergence 29 .…”
Section: Introductionmentioning
confidence: 99%